2014
DOI: 10.1159/000363415
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life after Laparoscopic and Open Resection of Colorectal Cancer

Abstract: Background: The aim of the study was to evaluate quality of life (QOL) outcomes after colorectal surgery for cancer from a 6-month perspective at a single institution. Methods: Cohort study to prospectively assess postoperative QOL in patients who underwent elective colorectal resection at the University Hospital Ostrava. QOL was assessed using the validated Short Form 36 (SF-36v2™) questionnaire at fixed time points. Results: A total of 148 patients were enrolled in the study (83 and 65 patients underwent lap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…A negative impact of anastomotic leakage on postoperative quality of life in colorectal cancer patients has previously been shown . Our results with regard to the laparoscopic approach are aligned with several studies that have shown an improved quality of life in the early postoperative period . However, a systematic review comprising 13 randomized trials with more than 2000 patients found no clinically relevant benefit for laparoscopic compared to open surgery with regard to quality of life , so this point remains controversial.…”
Section: Discussionsupporting
confidence: 81%
“…A negative impact of anastomotic leakage on postoperative quality of life in colorectal cancer patients has previously been shown . Our results with regard to the laparoscopic approach are aligned with several studies that have shown an improved quality of life in the early postoperative period . However, a systematic review comprising 13 randomized trials with more than 2000 patients found no clinically relevant benefit for laparoscopic compared to open surgery with regard to quality of life , so this point remains controversial.…”
Section: Discussionsupporting
confidence: 81%
“…HRQoL is a multidimensional construct encompassing patients’ perceptions of domains such as physical, emotional, social, and cognitive functions [ 35 ], and these perceptions are influenced not only by exercise capacity [ 20 ], but also by clinical factors such as the administration of adjuvant chemotherapy [ 36 , 37 ], specific symptoms such as fatigue and pain [ 38 , 39 , 40 ], the extent of surgical resection [ 12 , 13 , 40 , 41 ], and psychosocial determinants such as anxiety, depression, self-efficacy, and social support [ 14 ]. Furthermore, evidence on the effects of pre- and/or postoperative exercise training on HRQoL has been limited to reviews that only included preoperative assessments [ 28 , 30 ], have not provided information on important health dimensions such as global quality of life and cancer-specific symptoms such as fatigue [ 34 ], and included non-randomized control trials in the quantitative synthesis [ 27 ], which tend to result in larger effect estimates [ 42 ].…”
Section: Introductionmentioning
confidence: 99%
“…This study attempted to determine the quality of life of patients with colorectal cancer surgery and examined the effects that problems experienced by patients in the early period after being discharged had on their quality of life, using both quantitative and qualitative research methods. It has been reported in the literature that the quality of life of patients after colorectal cancer surgery is lower than before surgery (Ihnát et al, 2014;Sharma et al, 2007;Yoo et al, 2005). In this study, the mean quality-of-life scores of the patients were found to be lower after surgery than before surgery.…”
Section: Discussionmentioning
confidence: 38%